ChemInform Abstract: Oxidative Heck Vinylation for the Synthesis of Complex Dienes and Polyenes. Issue 46 (24th October 2013) - Delcamp, Jared H.; Gormisky, Paul E.; White, M. Christina
Abstract Different substituted dienes are obtained by using this Heck vinylation and also the long polyene chain (XII) can be synthesized in a highly stereoselective manner.